PENERAPAN MODEL RODRIGUES-BADACZEWSKI DALAM PEMBELAJARAN APRESIASI DRAMA DI SMA - Amal Akbar (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2012)
Abstract: The Application of Badaczewski Rodrigues Model in teaching Appreciation of Drama for High School Students. This study aimed (1) to analyse  the ability of drama  appre-ciation to the students of XI Class in  SMAN 5 Makassar and (2) to test the effectiveness of the Badaczewski  Rodrigues Model in teaching  drama appreciation. This research was  designed as Quasi-experimental study. The amout of population is 270 students consist of nine classes. Sam-pling is done by cluster sampling, while  data collected through testing and observation. Results showed firstly that students' learning outcomes using the model Rodrigues-Badaczewski consi-dered adequate . There are 28 students ( 93,34%)  out of 30 students of Experimental class  got score more than 7,5.  In the Control class learning outcomes are not adequately considered. Only 17 students (56,67%) got score more than 7,5. Secondly, the applications of  model-Badaczewski Rodrigues proved  effectively  in teaching drama appreciation. Statistic  test showed  that t 18,324 with a significance value (p) 0,000. Finally, it can be concluded that there were significant differ-rences between experimental classes with control classes. Abstrak: Penerapan Model Rodrigues-Badaczewski dalam Pembelajaran Apresiasi Drama di SMA. Penelitian ini bertujuan mengkaji kemampuan mengapresiasi drama siswa Kelas XI SMA Negeri 5 Makassar dan (2) menguji efektivitas model Rodrigues-Badaczewski dalam pem-belajaran apresiasi drama. Penelitian didesain dengan eksprimen semu. Populasi penelitian ber-jumlah 270 orang yang terdiri atas sembilan kelas. Penarikan sampel dilakukan dengan cluster sampling. Pengumpulan data  melalui tes dan observasi. Hasil penelitian menunjukkan bahwa hasil pembelajaran apresiasi drama siswa kelas XI SMA Negeri 5 Makassar dengan model Rodrigues-Badaczewski dikategorikan memadai. Dari 30 siswa kelas eksperimen, terdapat 28 (93,34%) siswa memperoleh nilai lebih dari 7,5. Hasil pembelajaran kelas kontrol dikategorikan tidak memadai, hanya 17 (56,67%) siswa memperoleh nilai lebih dari 7,5. Kedua, model Rodrigues-Badaczewski efektif diterapkan dalam pembelajaran apresiasi drama.  Uji stastik menunjukkan nilai t 18,324 dengan signifikansi (p) 0,000. Dengan demikian disimpulkan ada perbedaan yang signifikan antara kelas eksprimen dengan kelas kontrol. Kata kunci: sastra, rodrigues-badaczewski, drama